Baptism and the pollution of Africa"s water - Klerk, Ben J. de (HTS teologiese studies, 2014)
Water often moves us to wonder, joy, terror or peace, and many times, water moves us to prayer. On the other hand, it is projected that, because of water shortages, by 2020, several African countries will experience a 50% reduction in crop yields. Between 75 and 250 million Africans will confront freshwater shortages. Water plays an important role in baptism: the requirements of Christian baptism are the use of water and calling upon the name of the Triune God. Baptism as a water bath is the fulfilment of the Old Testament washings. Nobody could and still can appear before God as an unclean person; baptism stresses the importance of cleansing. The research question that is discussed in this article is the following: in what way may baptism, as holy sign and seal of the washing away of sins by the blood and Spirit of Jesus Christ, contribute to sensitise believers to combat waste in our rivers and dams and the pollution of our waters? Two aspects of baptism are discussed, namely cleansing and going under and coming up from the water as sign and seal of partaking in Christ’s death and resurrection.